Love Lessons - Wilson J. Jacqueline (London, Corgi Books, 2007)
Prue and her sister Grace have been educated at home by their controlling, super-strict father all their lives. They know they are different to `normal` girls but their attempts to find out what being an ordinary teenager are like. But when Dad has a stroke and ends up in hospital, Prue suddenly discovers what it`s like to have a little freedom